2001
DOI: 10.1211/0022357011778070
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1 and cyclooxygenase-2 selectivity of non-steroidal anti-inflammatory drugs: investigation using human peripheral monocytes

Abstract: Since the pharmacological profiles of various non-steroidal anti-inflammatory drugs (NSAIDs) might depend on their differing selectivity for cyclooxygenase 1 (COX-1) and 2 (COX-2), we developed a new screening method using human peripheral monocytes. Monocytes from healthy volunteers were separated, and the cells were incubated with or without lipopolysaccharide (LPS). Monocytes without LPS stimulation exclusively expressed COX-1 on Western blotting analysis, whereas LPS stimulation induced COX-2 expression. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 33 publications
5
111
2
2
Order By: Relevance
“…* Ratio of IC50 for COX-1 to IC50 for COX-2 (positively correlated with COX-2 selectivity such that a ratio < 1 indicates COX-1 selectivity and a ratio > 1 indicates COX-2 selectivity). Based on references [33][34][35][36] Biochem Pharmacol. Author manuscript; available in PMC 2012 February 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…* Ratio of IC50 for COX-1 to IC50 for COX-2 (positively correlated with COX-2 selectivity such that a ratio < 1 indicates COX-1 selectivity and a ratio > 1 indicates COX-2 selectivity). Based on references [33][34][35][36] Biochem Pharmacol. Author manuscript; available in PMC 2012 February 1.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments performed utilized NSAIDs with variable effects on intestinal restitution and variable COX-selectivity, as shown in Table 1 [33][34][35][36]. Drug effects were evaluated over the following ranges of concentrations, as indicated in the text or figure legends: indomethacin (1-100uM); phenylbutazone (1-100uM); NS-398 (1-100uM), SC-560 (10 nM-1uM).…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…The C max following the fourth IV dose was 3090 g/ml and 5617 ng/ml, for 18.75 and 37.5 mg, respectively. AUC (0)(1)(2)(3)(4)(5)(6) following the fourth dose of 18.75 and 37.5 mg were 935 and 1839 ngÁhour/ml, respectively. The C max and AUC following the first and fourth doses were similar, suggesting no accumulation of IV HPbCD-diclofenac.…”
Section: Studymentioning
confidence: 95%
“…1,2 Recent studies have further demonstrated that diclofenac opens KCNQ2/3 potassium channels and inhibits sensory neuronal depolarization, resulting in analgesia. 3 Diclofenac has long been approved as safe and effective for both acute and chronic pain through a variety of routes.…”
mentioning
confidence: 99%
“…Nonsteroidal anti‐inflammatory drugs (NSAIDs) represent a key aspect of such multimodal approaches 1, 3. Diclofenac is an NSAID that exerts analgesic, antipyretic, and anti‐inflammatory effects via cyclooxygenase (COX)‐1 and COX‐2 inhibition; it has been widely prescribed in multiple formulations since its introduction in the United States in 1988 and has demonstrated efficacy and safety in managing acute and chronic pain 4, 5, 6, 7, 8, 9…”
mentioning
confidence: 99%